Formulasi Gel Antibakteri Ekstrak Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) Menggunakan Hydroxy Propyl Methyl Cellulose(HPMC) dan Uji Aktivitas terhadap Staphylococcus aureus - Febriana Eka Valentina; Dwi Saryanti (Pharmacon: Jurnal Farmasi Indonesia, 2023)
The content of flavonoids, alkaloids, and saponins in fragrant pandan leaves (Pandanus amaryllifolius Roxb.) can be antibacterial to inhibit the growth of microorganisms on the skin. The extract obtained from fragrant pandan leaves (DPW) is processed into a gel, with the consideration that the gel adheres well, does not block skin pores, is easily rinsed with water and has very good absorption. The purpose of this study was to determine the HPMC content as a gelling agent so as to obtain an antibacterial gel preparation of DPW extract with the best physical quality and antibacterial activity on Staphylococcus aureus (SA). The  DPW ethanol 96% extract gel made from 2%, 3%, 4% HPMC was tested for the physical stability of the gel stored at room temperature for 21 days which included evaluation of organoleptic, homogeneity, degree of acidity, viscosity, spreadability, adhesion. Gel activity against SA was carried out using the well method. Antibacterial gel from DPW extract using 2% HPMC concentration has the best physical quality compared to DPW extract gel with other HPMC concentrations. Antibacterial gel from DPW extract with 2% HPMC concentration in gel form, dark green color, pandan aroma, homogeneous and uniform, pH 6 ± 0, pH is not harmful to skin, viscosity 325 ± 0 dPa.s, spreadability 7.5 gcm /s , adhesion 15.17 ± 0.00 seconds, antibacterial activity against SA with an inhibition zone of 27.26 ± 25.30 mm was classified as very strong. The result of preparations were stable for 21 days.